CRISPR-Cas9 Genome Editing Technology: Development and Applications - Soni, Anjali; Shaikh, Hala (IJRDO-Journal of Applied Science, 2016)
The discovery of an ancient adaptive immune system in bacteria, called the CRISPR/Cas system, has revolutionalized the modern science. The bacterial proteins that identify and target viral DNA for degradation have been characterized and manipulated for a variety of uses in agriculture, molecular biology and medicine. Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated (Cas) protein 9 system provides a robust and multiplex genome editing tool, enabling researchers to precisely manipulate specific genomic elements and facilitating the elucidation of target gene function in biology and diseases. CRISPR-Cas9 gene editing technique has set the stage for remarkable developments. This technology is used to modify, regulate, or mark genomic loci in a wide variety of cells and organisms from all three domains of life. These results highlight a new era in which genomic manipulation is no longer a bottleneck to experiments, paving the way toward fundamental discoveries in biology, with applications in all branches of biotechnology, as well as strategies for human therapeutics.